IPTEKS PELAKSANAAN PEMUNGUTAN PAJAK AIR PERMUKAAN PADA CABANG PELAYANAN PENDAPATAN DAERAH WILAYAH KABUPATEN BANDUNG BARAT - Buntuan, Dhifa; Wokas, Heince (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
The process of collecting surface water tax, hereinafter abbreviated as APER, must basically be carried out in accordance with the procedures stipulated under Regional Regulations. One from many types of local tax that included in Regional Original Income (PAD) is Surface Water Tax, which is one of the sources of finance for government and regional development to improve the welfare of the community. The procedure of collecting surface water tax is directly carried out at the Regional Revenue Service Branch (CPPD) of West Java Province, West Java Regency that is in cooperation with the One Stop Integrated Service and Capital Licensing Service (DPMPTSP) and Water Resources Management Agency (PSDA). In the implementation process, starting from the process of stipulating the Water Taking Permit (SIPPA) for new Taxpayers, registering and conducting data collection, submission, Water Acquisition Value (NPA) to Dispenda, Reporting and Regional Tax Return (SPPD), tax determination, provision tax, the distribution of the Regional Tax Assessment Letter (SKPD) to the Company for billing, and then the taxpayer makes a payment transaction. From the results of this study, the authors suggested that the Regional Revenue Service Unit of West Java Regency Padalarang, have to provide the direction and give counseling to the taxpayers both directly or indirectly to taxpayers who use and take surface water without causing damage for the environment.Keywords: The Process Of Collecting Surface Water Tax